(untitled) (Medico Legal Update, 2020)
The top priority of this study was to identify how nurses’ organizational commitment (OC) serves as a mediating factor between Quality of Nursing Work Life (QNWL) and turnover intention (TI) among Korean nurses. Three hundred thirteen registered nurses working in hospitals participated in this study. Mediating effect analysis was conducted to identify the relationship between QNWL, OC, and TI. The results revealed significant correlations between variables. OC showed a perfect mediating effect in the relationship between QNWL and TI. The results suggest that nurses’ QNWL has a significant influence on the TI, which is mediated via OC.